2013
DOI: 10.1002/cmdc.201300177
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Studies of Pyrrolone Antimalarial Agents

Abstract: Previously reported pyrrolones, such as TDR32570, exhibited potential as antimalarial agents; however, while these compounds have potent antimalarial activity, they suffer from poor aqueous solubility and metabolic instability. Here, further structure–activity relationship studies are described that aimed to solve the developability issues associated with this series of compounds. In particular, further modifications to the lead pyrrolone, involving replacement of a phenyl ring with a piperidine and removal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…A lipophilicity/potency trend was also generally seen in the pyrrolone series, 62 though potency was seen for several compounds containing a substituted piperidine ring in place of the N -aryl group. 63 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A lipophilicity/potency trend was also generally seen in the pyrrolone series, 62 though potency was seen for several compounds containing a substituted piperidine ring in place of the N -aryl group. 63 …”
Section: Resultsmentioning
confidence: 99%
“…The tolerance of the NN set to the introduction of the pyridine in OSM-S-51 (Figure 4) could be explored further as a means to increase solubility in that cluster, and a pendant substituted piperidine was found to lead to several potent compounds in the pyrrolone series that possesses some structural similarities to the NN series. 63 Indeed variation of the aromatic group in the arylpyrrole series was not explored given the intractability of substituting the ester: given the tight SAR, low solubility, and poor metabolic stability observed for the series, the project viewed the probabilities of success as limited and so did not pursue these targets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, compound 2 remains unexplored for antiprotozoal activity, with no examples of analogues appearing in the literature. Importantly, in our context, several studies have shown that compounds containing the arylpyrrole framework display a broad spectrum of biological properties, including antiparasitic activities, as illustrated by the anti-malarial lead compound 3 [36]. Furthermore, numerous chalcone derivatives, including compounds 4 and 5, have been reported as possessing anti-bacterial and anti-tuberculosis activity [37].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported the identification of a hit ( TDR32750 ) [6,7] from a screen of the ChemDiv5000 ‘maximally structurally diverse’ compound collection against P. falciparum . This screen was carried out by the World Health Organisation Programme for Research and Training in Tropical Medicine ( Fig.…”
Section: Introductionmentioning
confidence: 99%